Implementation of the Marine Strategy Framework Directive in Macaronesia and synergies with the Maritime Spatial Planning process. (December 2020) - Abramic, A.; Nogueira, N.; Sepulveda, P.; Cavallo, M.; Fernández-Palacios, Y.; Andrade, C.; Kaushik, S.; Haroun, R.
Abstract: The relationship between the Marine Strategy Framework Directive 2008/56/EC (MSFD) and the Maritime Spatial Planning (MSP) process has been analyzed to understand which is the dominant process or where there is an overlap. In this contribution, we used the case study of the three archipelagos: Azores, Madeira and the Canary Islands, included in the European Macaronesian Sea, in order (a) to recognize/identify common principles at policy level; (b) to evaluate the first implementation cycle of MSFD (2012–2018) and its potential contribution to the MSP process in this region. An empirical in-depth assessment was applied to analyze the degree of MSFD implementation by both States (Portugal and Spain) in those regional waters and identifying what is relevant for the concomitant MSP process. The results of this study show that MSFD is particularly challenging in these archipelagos with extensive EEZs. Still, MSFD implementation reports identify relevant actions and related data that can provide the groundwork to ensure robust consideration of the marine environment in the planning process. We recommend these findings to integrate the ongoing Macaronesian MSP.